Identification of Groundwater Distribution Using Self Potential Method - Muhammad Fathur Rouf Hasan; Tri Widya Swastika; Nunung Martina; Linda Sari Wulandari (POLITEKNIK NEGERI JAKARTA, 2019)
The drought is one of the biggest problems for the community, this problem will be slightly resolved if the regions have a groundwater sources. This research has been carried out in the karst area, Druju Village, Sumbermanjing District, Wetan Regency, Malang. The purpose of this study is to determine the distribution of groundwater in the Wonorejo Village, Malang District. The method that used is the Self Potential (SP) method using leap frog configuration with 104 measurement points. The results of this study indicate the value of electric potential shown between 0-13.5 mV, and assume that a low potential value (0-1 mV) is an indication of groundwater distribution. Areas with low potential values are found in four area. The area with the lowest potential value can be used as a reference in making wells. The possibility of groundwater distribution in this research area is not in one line / flow. However, it is possible that in areas outside the research location, groundwater flow is in one lane. Thus, to prove this assumption it is necessary to carry out further research in a wider area and the use of other geophysical methods to obtain more varied subsurface information.